Rancang Bangun Sistem Informasi Pemasaran Dan Penjualan Rumah Hunian Berbasis Web - Sukrawan, Pande Gede; Arifin, Mochammad; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
PT. Sami karya located on the street Deandels, 64 districts Brondong, Lamongan. The company is engaged in property and has a network of residential homes scattered in the area of East Java. Such areas include: Lamongan, Jember, Tulungagung, and Trenggalek. Each residential area of approximately 120 homes of various types are ready for habitation. Currently recording sales transactions that do still use Microsoft Office Excel to find sales reports and to view a list of homes that already and not yet sold, so it will take time especially when it will repair the data such as the cancellation of the booking house or cancellation of the booking because the buyer does not get approval mortgage from the bank. Buyers are very difficult to obtain clear information about home sales, buyers who come to the office of marketing often find marketing is not in place because at each sales office there only 3 marketing alone. The solution to overcome this problem then bemade Information Systems Marketing and Sales Shelter that will assist in the marketing of homes for sale as well as handle the process of managing the home sales data. The application also uses SMS as an intermediary solution to deliver information to remind the buyer in completing the file incomplete.